MEMBENTUK KARAKTER BELAJAR SISWA DI ERA PANDEMI - Jodang Setia Adi Anista R. (STAI Ma'had Aly Al-Hikam Malang, 2021)
Character education is the most important part in the educational process, from an early age children are educated with character education, children will have potential behavior, with this pandemic condition children's education is limited, so teachers must continue to carry out the educational process in addition to adding knowledge to children, teachers also instill character education in their students, to form a character that is not expected to be immediately understood by children, character education goes through several stages that will be carried out by children, in essence, the resistance that children will go through is religious, sensitive to the environment, friendship, discipline.